2021
DOI: 10.1101/gad.348190.120
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell atlas reveals meningeal leukocyte heterogeneity in the developing mouse brain

Abstract: The meninges are important for brain development and pathology. Using single-cell RNA sequencing, we have generated the first comprehensive transcriptional atlas of neonatal mouse meningeal leukocytes under normal conditions and after perinatal brain injury. We identified almost all known leukocyte subtypes and found differences between neonatal and adult border-associated macrophages, thus highlighting that neonatal border-associated macrophages are functionally immature with regards to immune responses compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 57 publications
(103 reference statements)
1
15
0
Order By: Relevance
“…S1B). While cell-type populations were consistent with other studies (DeSisto et al, 2020;Mrdjen et al, 2018;Van Hove et al, 2019;Zelco et al, 2021), the relative abundance of innate to adaptive lymphocytes was markedly different.…”
Section: Meningeal Type 2 Innate Lymphocytes Expand and Produce Il-13...supporting
confidence: 89%
“…S1B). While cell-type populations were consistent with other studies (DeSisto et al, 2020;Mrdjen et al, 2018;Van Hove et al, 2019;Zelco et al, 2021), the relative abundance of innate to adaptive lymphocytes was markedly different.…”
Section: Meningeal Type 2 Innate Lymphocytes Expand and Produce Il-13...supporting
confidence: 89%
“… 79 However, even in mice and humans, the gut has been suggested to take part in early B cell development, and both VDJ recombination and selection of transitional B cells into specific B cell lineages have been described. 80 83 Unexpectedly, some recent single-cell RNASeq studies have also found gene expression patterns suggestive for early B cell development in the meningeal tissues of the CNS, 84 , 85 with two studies even reporting a brain associated lymphopoietic niche. 86 , 87 This observation raises the possibility that not only bone marrow, but also other tissues able to maintain long-lived plasma cells are able to support primary B lymphopoiesis.…”
Section: Inductive and Effector Sites For Mucosal Iga Responsesmentioning
confidence: 99%
“…During early embryogenesis, pluripotent embryonic cells undergo differentiation into all somatic cell types. This capacity is rapidly restricted along with the formation of the three distinct germ layers, each giving rise to specified cell types, which Conrad Waddington famously illustrated in his epigenetic landscape (Zalc et al, 2021). However, CNCCs, a transient migratory stem cell-like population in vertebrates, challenge this paradigm.…”
Section: Single-cell Atlas Of Calvarial Bones and Sutures During Embr...mentioning
confidence: 99%
“…Through unbiased scRNA-seq analysis, researchers have revealed that, in the early stages of developing murine embryos, the neural crest cells (NCCs), including CNCCs and TNCCs, undergo a series of fate bifurcations and binary decisions (Soldatov et al, 2019;Zalc et al, 2021). Up to early migration, the first decision separates sensory neural and glial fate from all other fates, while the second decision occurs between mesenchymal and autonomic lineages (Soldatov et al, 2019).…”
Section: Single-cell Atlas Of Calvarial Bones and Sutures During Embr...mentioning
confidence: 99%